1994
DOI: 10.1182/blood.v83.9.2489.2489
|View full text |Cite
|
Sign up to set email alerts
|

Immature human cord blood progenitors engraft and proliferate to high levels in severe combined immunodeficient mice

Abstract: Unseparated or Ficoll-Hypaque (Pharmacia, Piscataway, NJ)--fractionated human cord blood cells were transplanted into sublethally irradiated severe combined immunodeficient (SCID) mice. High levels of multilineage engraftment, including myeloid and lymphoid lineages, were obtained with 80% of the donor samples as assessed by DNA analysis, fluorescence-activated cell sorting (FACS), and morphology. In contrast to previous and concurrent studies with adult human bone marrow (BM), treatment with human cytokines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 0 publications
2
56
1
Order By: Relevance
“…This property is difficult to assess for human haemopoiesis, however several animal models have been developed that assess the capacity of human haemopoietic cells to engraft a xenogeneic host. In contrast to adult BM and mobilized PB, UCB cells engraft immunodeficient mice at relatively high levels with low cell numbers in the absence of exo­genous cytokine 21 …”
Section: Intrinsic Properties Of Umbilical Cord Bloodmentioning
confidence: 99%
“…This property is difficult to assess for human haemopoiesis, however several animal models have been developed that assess the capacity of human haemopoietic cells to engraft a xenogeneic host. In contrast to adult BM and mobilized PB, UCB cells engraft immunodeficient mice at relatively high levels with low cell numbers in the absence of exo­genous cytokine 21 …”
Section: Intrinsic Properties Of Umbilical Cord Bloodmentioning
confidence: 99%
“…have reported stable human long‐term hematopoiesis in SCID mice transplanted with total or MNC from human UCB. Both myeloid and lymphoid cells of human origin were observed in the animal's tissues and human CFC, including multipotent, myeloid, and erythroid progenitors, were also detected by in vitro cultures [107]. These results indicate the engraftment of an early hematopoietic progenitor/stem cell.…”
Section: In Vivo Characterization Of Ucb Hspcmentioning
confidence: 99%
“…The primitive cells that initiated the graft were operationally defined as SCID repopulating cells (SRCs). Kinetic experiments showed that only 0.1% of the injected CFCs and LTC‐ICs were detectable in the murine BM 2 days post‐transplant and that there was a large expansion of these cells, as well as primitive CD34 + cells, over the next 4 weeks, implying their production from a more primitive cell32. Since this pioneering work, a number of research groups have confirmed these results33–35.…”
Section: Characterization Of Hscsmentioning
confidence: 77%